Upaya Meningkatkan Kemampuan Mengenal Lambang Bilangan Melalui Kegiatan Mencocokkan Tulisan Dengan Lambang Bilangan - Lasiah Lasiah; Melvi Lesmana; Yolanda Pahrul (LPPI Yayasan Almahmudi bin Dahlan, 2023)
The background of this research is the low ability of the children group B of Harapan Bangsa Kindergarten in recognizing number symbols 1-10. Some children have not been able to match numbers with their number symbols. One of the solutions offered by researchers is to try the activity of matching writing with number symbols to improve understanding of number symbols in children group B of Harapan Bangsa Kindergarten. The type of research applied is Classroom Action Research (CAR). Data collection techniques used were observation techniques and documentation techniques, while data analysis techniques used in this research were quantitative data analysis techniques and qualitative data analysis techniques. The research results obtained were the BB value in the pre-action 7 children or 41.18% In the first cycle it became 2 children or 11.76% and in the second cycle it became 0 children or 0%, the MB value in the pre-action was 6 children or 35.209% , in cycle 1 there were 5 children or 29.41% then in cycle II there was 1 child or 5.88%, the BSH value in the pre-action there were 2 children or 11.76% In cycle 1 there were 6 children or 35.29% then in cycle II there were 5 children or 29.41%, the final value of BSB in pre-action activities there were 2 children or 11.76% in cycle 1 there were 4 children or 23.53% and at the end of cycle II there were 11 children or 64.71% of these results show a very significant improvement. Thus it can be concluded that the activity of matching writing with number symbols can improve the ability to recognize number symbols in children. It is also suggested to teachers to make this activity an alternative activity to improve children's cognitive abilities in recognizing number symbols Keywords: number symbol, matching activity, class actionroom research